2020
DOI: 10.1007/s10608-020-10146-9
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Affective Learning Biases with Cognitive Training and Prefrontal tDCS: A Proof-of-Concept Study

Abstract: Background Cognitive models of mood disorders emphasize a causal role of negative affective biases in depression. Computational work suggests that these biases may stem from a belief that negative events have a higher information content than positive events, resulting in preferential processing of and learning from negative outcomes. Learning biases therefore represent a promising target for therapeutic interventions. In this proof-of-concept study in healthy volunteers, we assessed the malleabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…However, very little research has assessed whether cognitive behavioral interventions change RL processes, despite several researchers advocating for computationally modeling learning and cognitive change in cognitive behavioral therapy [ 25 , 26 ]. Recent studies have shown that cognitive interventions can change RL processes in healthy individuals [ 27 ] and individuals with schizophrenia [ 28 ]. To our knowledge, this study is the first to behaviorally assess changes in RL through cognitive bias modification in a population with elevated anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little research has assessed whether cognitive behavioral interventions change RL processes, despite several researchers advocating for computationally modeling learning and cognitive change in cognitive behavioral therapy [ 25 , 26 ]. Recent studies have shown that cognitive interventions can change RL processes in healthy individuals [ 27 ] and individuals with schizophrenia [ 28 ]. To our knowledge, this study is the first to behaviorally assess changes in RL through cognitive bias modification in a population with elevated anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%